STUDY ON CLINICAL PROFILE OF ACUTE PANCREATITIS FROM A TERTIARY CARE TEACHING INSTITUTE OF WESTERN UTTAR PRADESH - Singh, Jaipal; Mawar, Alok; Patel, Jaya; Manyal, Rohit; Lohokare, Rajeev (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The objective of this study was to study the clinical profile of subjects diagnosed and managed for acute pancreatitis at a tertiary care teaching institute of western Uttar Pradesh. Methods: All the cases diagnosed and managed for acute pancreatitis at the study place and during the study time formed the study population. All the cases were followed up till the outcome of the case. A detailed pro forma was designed to capture relevant details of study subjects. Results: Underlying cause of the clinical condition was noted as alcoholic in nature by majority (80%) of the study subjects. In ten patients (16.7%) reason for the pancreatitis could not be ascertained despite extensive evaluation. Common complications of the clinical condition were noted as pleural effusion (n=12, 20%), followed by ascites (n=9, 15%) and acute fluid collection (n=5, 8.3%). Morality was seen among two patients (3.3%). Conclusion: In this region of the western Uttar Pradesh, alcohol is the most frequent cause of acute pancreatitis. Males are more likely to get the condition, and it typically manifests in the fourth decade of life. Biochemical and radiological results supplement the primary clinical diagnosis.